SMART TECHNOLOGY USED IN MAKING SMART LIBRARY - Hirekhan, Shilpa N.; Prakashe, Veena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of this paper is to highlight the various technology used in academic libraries and to improve understanding of its functionality and development, as well as to place it into the broader content of existing technologies that we can corporate it into our universities, college libraries and services. It also discusses innovative technological developments. However, smart library and its role in academic research are no doubt going through a clear transformation in the 21st century.